SIMULTANEOUS ESTIMATION OF THIOCOLCHICOSIDE AND ACECLOFENAC BY HPTLC - Syal, Pratima; Kumar, Ravinder; Arora, Govind (International Journal of Current Pharmaceutical Research, 2017)
Objective: Therefore the aim of the present work was to develop simple, precise and accurate HPTLC method for simultaneous determination of THIO and ACE in pharmaceutical dosage form and application of the method for dissolution study with help of HPTLC method. Methods: The TLC procedure was optimized in view to develop a simultaneous assay method for THIO and ACE. HPTLC Pre-coated plates silica gel 60 F254 20×10 cm, layer thickness 0.2 mm (Merck, Germany). The samples were spotted in the form of bands (8 mm) with a Camag 100 microliter sample (Hamilton) syringe on silica gel precoated aluminium 60F254 plates. The mobile phase consisted of methanol: chloroform: water (9.6: 0.2: 0.2 v/v/v) and 10 ml of mobile phase were used per chromatography run. Plates were scanned over the range of 200-400 nm and the spectra were overlain. Results: The detector response was found to be linear in the concentration range of 0.03-0.180 µg/band and 0.75-4.5 µg/band for THIO and ACE and noting the peak areas. Accuracy of the assay method was evaluated with the recovery of the standards from excipients. The mean percentage recoveries obtained for THIO and ACE were 99.34% and 99.08%, respectively, reported. The peak purity of both drugs was assessed by comparing the respective spectra of standard drugs and samples at peak start, peak apex and peak end positions of the spot. Conclusion: HPTLC, with its advantage of low operating cost, high sample thought and minimum sample preparation need is now days preferred as routine analytical techniques for control and assurance. The validated HPTLC method employed here proved to be simple, fast, accurate, precise and sensitive, thus can be used for routine analysis of Thiocolchicoside and Aceclofenac in tablet dosage form.